Acid activated smectite clay as pozzolanic supplementary cementitious material. (December 2022) - Ayati, Bamdad; Newport, Darryl; Wong, Hong; Cheeseman, Christopher
Abstract: This research has investigated the structural changes and pozzolanic activity produced in acid activated smectite clay. The activation treatment used HCl at different concentrations, using different times and at a range of temperatures. X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy were used to determine the acid dissolution mechanism and characterise the activated clay mineral structure. Acid activation causes dehydroxylation of smectite clay, followed by leaching of octahedral cations. This results in the formation of a silica-rich amorphous phase that exhibits substantial pozzolanic activity compared to the same clay sample that had undergone calcining treatment at 850. The optimum sample was activated for 8 h using 5 M HCl at 90 °C. This was 93 % amorphous. Mortar prisms prepared with 25 % replacement of Portland cement by acid activated smectite produced 93 % compressive strength of plain Portland cement mortar.